Students' self-directed learning readiness towards using the “SolveMe” Web in Technical and Vocational Education - Ariffin, Ahmad Hamdan; Wan Hassan, W.A.S.; Ahmad, F.; Hamzah, N.; Rubani, Siti Nur Kamariah; Zakaria, Normah (WARSE, 2020)
Self-directed Learning Readiness (SDLR) is an essential skill in continuous Tearning and Leaching (T&L) that needs to be applied to any student. The study aimed to look at the Self-directed Learning Readiness Level (SDLRL) among the final semester students. The total number of students involved was 136 students, covering seven areas namely Catering, Electrical and Electronics, Building Construction, Creative Multimedia, General Machining, Welding, and Air Conditioning. The questionnaire instrument used was adapted from Guglielmino(1997). The results of the study were analyzed using descriptive statistics involving average use, standard deviation, percentages, frequency and scores. Inference statistics involve t-tests. Studies showed that the students' Key Performance Indexes (KPIs) were at moderate levels for three aspects of self-management, learning to learn and self-control. The t = .119 test, p <.905 showed no significant difference in SDLRL based on gender (female, average = 3.4002, SP = .37393 and male, average = 3.3925, SP = .37146) which served as a reference that could benefit the academic institution for adapting the T&L technique involving SDLR.